2019
DOI: 10.1007/s11095-019-2576-9
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Pharmacokinetic Cell Culture System that Simulates Physiologic Drug and Nanoparticle Exposure to Macrophages

Abstract: Purpose An in vitro dynamic pharmacokinetic (PK) cell culture system was developed to more precisely simulate physiologic nanoparticle/drug exposure. Methods A dynamic PK cell culture system was developed to more closely reflect physiologic nanoparticle/drug concentrations that are changing with time. Macrophages were cultured in standard static and PK cell culture systems with rifampin (RIF; 5 μg/ml) or β-glucan, chitosan coated, poly(lactic-co-glycolic) acid (GLU-CS-PLGA) nanoparticles (RIF equivalent 5 μg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…[ 32 ] Based on these findings our laboratory as well as others have developed nanoparticles with glucan to significantly enhance the immune modulation of macrophage, with the ultimate goal of reducing intracellular M.tb . We have previously shown β‐glucan as a ligand on PLGA‐CS nanoparticles enhanced cytokine production from macrophage [ 6,11 ] and reduced the number of CFU of Mycobacterium smegmatis , a mimetic of TB. While these nanoparticles are efficacious against M. smegmatis , we have found that synthesis of these nanoparticles is a complex, multi‐step synthesis process that is not feasible for scale up processes and the synthesis process ultimately reduces the amount of drug that can be delivered.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 32 ] Based on these findings our laboratory as well as others have developed nanoparticles with glucan to significantly enhance the immune modulation of macrophage, with the ultimate goal of reducing intracellular M.tb . We have previously shown β‐glucan as a ligand on PLGA‐CS nanoparticles enhanced cytokine production from macrophage [ 6,11 ] and reduced the number of CFU of Mycobacterium smegmatis , a mimetic of TB. While these nanoparticles are efficacious against M. smegmatis , we have found that synthesis of these nanoparticles is a complex, multi‐step synthesis process that is not feasible for scale up processes and the synthesis process ultimately reduces the amount of drug that can be delivered.…”
Section: Resultsmentioning
confidence: 99%
“…In the current study, we developed a simple curdlan (linear beta‐1,3‐glucan) based nanoparticle that is physically blended with PGA, thus bypassing the need for a PLGA‐CS based nanoparticles ultimately reducing the number of steps in nanoparticle synthesis. Our C‐NPs formed by blending of curdlan and PGA which eliminates the need for chemical modification or conjugation of curdlan that has been done previously [ 5,6,10,12,13,15,35 ] while maintaining the immunostimulatory capabilities of curdlan that is often lost with chemical modification with small molecules. [ 10,15 ] Blending of curdlan and PGA has suitable processability and obtains the multicarboxylates originated from PGA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kutscher et al report the development of an in vitro dynamic pharmacokinetic cell (macrophage) culture system with the aim of precise simulation of drug elimination profiles in human. Rifampicin loaded PLGA based nanoparticles were used in the model (8). Such a PK model is intended to support translational studies to develop nanomedicines for infectious diseases.…”
mentioning
confidence: 99%